PREVALENCE AND OCCUPATIONAL CORRELATES OF TRADITIONAL MEDICINE SYNDROMES AMONG PATIENTS WITH CHRONIC RHINOSINUSITIS: A CROSS-SECTIONAL STUDY (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the prevalence of Traditional Medicine (TM) syndromes and their association with occupation in patients with chronic rhinosinusitis (CRS) at Le Van Thinh Hospital.Methods: An analytical cross-sectional study was conducted at Le Van Thinh Hospital from December 2024 to April 2025.Results: Among 384 patients with chronic rhinosinusitis, six syndromes and one special pattern were identified. The most common were Lung meridian constrained by heat (29.17%), followed by Lung Qi Deficiency (27.60%) and Qi Stagnation with Blood Stasis (17.97%). The least common were Spleen Qi Deficiency with Dampness Retention (3.91%) and Kidney Yang Deficiency (3.65%). The Phlegm-Turbidity Obstructing the Lung syndrome was significantly associated with female gender (p < 0.05).Conclusion: In patients with chronic rhinosinusitis, the common TM syndromes include Lung Lung meridian constrained by heat (29.17%), Lung Qi Deficiency (27.6%), Qi Stagnation with Blood Stasis (17.97%), and Phlegm-Turbidity Obstructing the Lung (16.15%). There is an association between Phlegm-Turbidity Obstructing the Lung and Lung Qi Deficiency with occupation.